A Stress Reduction Program Adapted for the Work Environment: A Randomized Controlled Trial With a Follow-Up - Lacerda, Shirley S.; Little, Stephen W.; Kozasa, Elisa H. (Frontiers in Psychology, 2018)
Objective The aim of this study was to evaluate an in-situ stress reduction program, named PROGRESS, developed to meet the specific needs of workers in a business context and to research its impact upon non-severe psychiatric symptoms, stress, anxiety, depression, processing speed/attention and mindfulness. Methods Participants with stress complaints were randomized into two groups: the main intervention group: group 1-G1, (n=22); and the control group: group 2-G2, (n=22). The protocol was divided into three distinct phases for the purpose of the study. Both groups were evaluated at time 1-T1, before the first eight-week intervention, which only G1 received. The second evaluation was made on both groups at time 2-T2, immediately after this first program; in order to test the program’s replicability and investigate possible follow-up effects, an identical second eight-week program was offered to G2 during time 3-T3, while G1 was simply instructed to maintain the practice they had learned without further instruction between T2 and T3. A Confirmatory factor analysis was conducted to investigate the construct validity of PROGRESS. Results Repeated measures MANOVA test, comparing G1 and G2, showed the effect of the intervention from T1 to T2 (p=0.021) and from T2 to T3 (p=0.031). Univariate analysis showed that participants from G1 improved levels of non-severe psychiatric symptoms, anxiety, depression, stress, processing speed/attention and mindfulness when compared with G2, from T1 to T2 (p<0.05). After the participants in G2 received the intervention (T2-T3), this group also showed improvement in the same variables (p<0.05). At the end of their follow-up period (T2-T3) - during which they received no further support or instruction - G1 maintained the improvements gained during T1-T2. The two main components were stress (stress in the last 24-hours, in the last week and last month) and mental health (non-severe psychiatric symptoms, depression, anxiety and mindfulness). Conclusion PROGRESS, an in-situ mindfulness program adapted to fit within the reality of business time constraints, was effective at replicating in more than one group the reduction of stress, depression, anxiety, non-severe psychiatric symptoms, processing speed and also the improvement of attention skills, showing sustained improvement even after 8-weeks follow-up.